KEPUASAN KERJA DILIHAT DARI IKLIM ORGANISASI - Aswadi Lubis (Yurisprudentia: Jurnal Hukum Ekonomi, 2015)
Organizational climate is an important factor that determines the life of an organization. As argued by Gibson, et al that organizational climate is the nature of the work environment or psychological environment in which the organization is perceived by the workers or members of the organization and is considered to influence the attitudes and behavior of workers against job. Organizational climate reflects the internal state of an organization because the climate can only be perceived by members of the organization, and the climate can be a means to find the cause of the negative behaviors that appear on the employee. Job satisfaction and quality of work life of one individual with another individual may be different. The difference is one of them can be due to differences in perceiving the organizational climate where she worked. For those who perceive positively, then by itself will create a sense of comfort and pleasure in work. These feelings will eventually lead to a sense of satisfaction in work and in the end will produce a good quality of working life.